Flowering and fruiting phenology in two varieties of grapes (Vitis vinifera) in tropical regions, Indonesia - SERI KAMILA; WINARSO DERAJAD WIDODO; EDI SANTOSA; M. RAHMAT SUHARTANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Kamila S, Widodo WD, Santosa E, Suhartanto MR. 2024. Flowering and fruiting phenology in two varieties of grapes (Vitis vinifera) in tropical regions, Indonesia. Biodiversitas 25: 4593-4602. Determining harvest time is a crucial phase in the production of high-quality grapes (Vitis vinifera L.). Traditional indicators, such as the number of days after pruning, the flowering period, and changes in skin color, are often unreliable. The variations in planting locations, particularly between lowland and highland areas, significantly influence temperature and climate conditions. These factors, especially in tropical regions with high rainfall, complicate the estimation of the harvest time, necessitating precise harvest handling. To determine grapes' ripeness level, a more accurate method, such as the heat unit method or accumulated heat unit, is required. This method considers the actual average temperature obtained by plants while in the field until they reach optimal maturity for harvest. Therefore, this study aimed to determine the heat units (°C per day) required from anthesis to harvest as a measurable criterion for assessing the ripeness of Jupiter and Transfiguration grape varieties. Additionally, it also focused on identifying the flowering and fruiting phenology of grapes in Indonesia, located in a tropical climate. The results showed that the two grape varieties can be harvested with a heating unit for Jupiter of 2521°C and Transfiguration of 2527°C. There was no difference between the two, but there was a significant difference in fruit diameter and metabolite compound content. These findings have significant practical implications for grape growers in tropical regions, providing them with a more accurate method for determining harvest time and improving the quality of their grapes.